The Influence of Resonant Leadership on Job Satisfaction with Visionary Leadership as a Moderating Variable: Penelitian - Muhammad Aga Sekamdo; Dasa Rahardjo Soesanto; Ifadhila; M. Asbullah; Montaris Silaen (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is a quantitative study with an explanatory approach, namely an approach that uses previous research as the main milestone for creating and proving the existing hypotheses in this study. The data used in this study is primary data that the researcher obtained from 345 employees working at Lippo Plaza Malls throughout Indonesia. The existing data was analyzed using smart PLS 4.0 analysis. The result in this article show that the first and second hypotheses in this article can be accepted and proven. In the first hypothesis, a resonant leadership style can have a positive relationship and a significant influence on Job Satisfaction. This is because the P-value is positive and below the 0.05 significance level, namely 0.022. These results indicate that a resonant leadership style can make employees feel comfortable and easy to complete their work. In addition, the visionary leadership style variable can also strengthen the influence of the resonant leadership style variable on job satisfaction because the p-values ​​tend to be positive and are below the significance level of 0.019, not too different from direct testing of 0.022.